2018
DOI: 10.14814/phy2.13848
|View full text |Cite
|
Sign up to set email alerts
|

Skeletal muscle adiponectin induction depends on diet, muscle type/activity, and exercise modality in C57BL/6 mice

Abstract: Changes in skeletal muscle adiponectin induction have been described in obesity and exercise. However, whether changes are consistent across muscle types and with different exercise modalities, remain unclear. This study compared the effects of diet and two isocaloric training programs on adiponectin induction and its regulators in three muscles: quadriceps (exercising/glycolytic‐oxidative), gastrocnemius (exercising/glycolytic), and masseter (nonexercising/glycolytic). Ten‐week‐old male C57BL/6 mice were fed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
10
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 29 publications
1
10
0
1
Order By: Relevance
“…Moreover, differential responses between AdipoRs have been described after 10 weeks of HFD in C57BL6 mice, where gastrocnemius muscle showed mild increases in protein levels of AdipoR2 (1.3-fold) whereas no changes were seen in AdipoR1 [26]. In contrast, our studies have found consistent decreases of AdipoR1 protein levels (~0.5-fold) after 10 and 20 weeks of HFD in quadriceps and gastrocnemius muscles from mice [32][33][34].…”
Section: Muscle Adiponectin Induction During Obesitysupporting
confidence: 77%
See 3 more Smart Citations
“…Moreover, differential responses between AdipoRs have been described after 10 weeks of HFD in C57BL6 mice, where gastrocnemius muscle showed mild increases in protein levels of AdipoR2 (1.3-fold) whereas no changes were seen in AdipoR1 [26]. In contrast, our studies have found consistent decreases of AdipoR1 protein levels (~0.5-fold) after 10 and 20 weeks of HFD in quadriceps and gastrocnemius muscles from mice [32][33][34].…”
Section: Muscle Adiponectin Induction During Obesitysupporting
confidence: 77%
“…In a subsequent study, we investigated the effects of 10 weeks of HFD on the adiponectin profile of glycolytic muscles (gastrocnemius and masseter) in mice. Here, increases in LMW adiponectin protein levels (~1.5-fold) were seen without major effects on the HMW isoform [34]. These findings suggest that in order to reach valid conclusions regarding muscle adiponectin induction, the type of muscle analysed, along with analysis of various adiponectin isoforms, are essential requirements for ensuring accurate reporting and interpretation of studies in this field.…”
Section: Muscle Adiponectin Induction During Obesitymentioning
confidence: 73%
See 2 more Smart Citations
“…Resumo das variáveis e seus pontos de corte utilizadas para diagnóstico da sarcopenia de acordo com os principais critérios vigentes e osteopenia, sendo considerados potenciais componentes alimentares para o desenvolvimento/manutenção da síndrome100,101 .Além do exposto, tem-se que tanto o tecido adiposo, quanto músculo esquelético e o osso apresentam funções endócrinas, com liberação de citocinas e expressão de receptores para ação destas e de hormônios sintetizados uns pelos outros80 . A seguir são apresentados os principais fatores fisiológicos propostos que intermeiam a fisiopatologia da obesidade osteosarcopênica e o resumo das vias está apresentado na figura 1. possível ocorrência de resistência à adiponectina no músculo esquelético110 . No osso, os efeitos também parecem ser contraditórios, uma vez que estudos in vitro revelaram potencial estímulo à osteoblastogênese111 , enquanto estudos em humanos mostram haver uma relação inversa entre as concentrações dessa citocina e a DMO em mulheres, independente do estado menopausal112 .…”
unclassified